Analisis Bentuk Metafora Lirik Lagu dalam Album Yang Patah Tumbuh, Yang Hilang Berganti Karya Banda Neira - Ike Azhani Putri; I Ketut Darma Laksana; I Gusti Ngurah Ketut Putrayasa (Stilistika : Journal of Indonesian Language and Literature, 2022)
Humans express in two ways, namely verbal and nonverbal. Song is a form of nonverbal linguistic expression. Through songs, various meanings can be created from the beauty of its structure. One of the aesthetic elements in the song is metaphor. Based on this, this research is entitled "Analysis of the Metaphor Forms of Song Lyrics in the Album Yang Patah Tumbuh, Yang Hilang Berganti by Banda Neira”. The problems in this study are divided into two, 1) What kinds of metaphors are contained in the album Yang Patah Tumbuh, Yang Hilang Berganti by Banda Neira 2) What is the meaning of the metaphorical expression in the album Yang Patah Tumbuh, Yang Hilang Berganti by Banda Neira. The method used in this study is referential matching with the determining element sorting technique (PUP). The theory used is semantic theory related to metaphorical expressions according to Ullmann's point of view (2009). The results show that there are four forms of using metaphorical expressions for song lyrics in the album Yang Patah Tumbuh, Yang Hilang Berganti by Banda Neira. The four forms are (1) anthropomorphic metaphor (such as backs of grass and whispering leaves), (2) shapes metaphor from concrete to abstract (for example, everything is eternal, inevitable and natural), (3) animal metaphor (seeing the butterfly calling the wind), and (4) synaesthetic metaphor (blue for everything that is far away). This metaphorical expression can be interpreted as a vehicle for human reflection in carrying out daily life behaviors regarding the search for identity, hope-life balance, and the manifestation of self-contemplation.